Bahasa Tanjong: The Heritage Language of the Jawi Peranakans of Penang - Hajar Abdul Rahim (Kajian Malaysia, 2015)
Bahasa Tanjong (Tanjong language) in the present discussion refers to a Malay dialect which has been labelled as "Penang Malay" and "George Town Malay" by past researchers. It is a variation of the Northern Malay dialect of Peninsular Malaysia which emerged over two centuries ago in the George Town area of Penang, also known locally as Tanjong. It is a hybridised form of Malay that grew out of the language contact situation between two cultures, Malay and South Indian Muslims. The intermarriage between the two groups produced an Indo-Malay community known as Jawi Peranakans who are the native speakers of the dialect. Bahasa Tanjong, as with other languages is a product of culture and is inextricably bound to its speech community. Thus, while considered a Northern Malay dialect, its emergence amidst a locale that was considered a colonial cosmopolitan caused it to possess features that are distinct from other Malay dialects. Early descriptions of bahasa Tanjong, such as Hamilton's discussion of "Penang Malay" published almost a century ago, considers the distinguishing characteristics of the dialect as a deviation of the Northern Malay Dialect. This is the point of departure for this article that argues that the features are in fact cultural markers that contribute to the construction of the bahasa Tanjong identity. Its Indian linguistic heritage, particularly Tamil, as well as its inclination to allow influences from other languages, sets it apart from other Northern Malay dialects. The uniqueness of bahasa Tanjong mirrors the equally distinctive community of speakers to which it belongs, namely the Jawi Peranakans of Penang. As the heritage language and living language of a minority Malay community, bahasa Tanjong cannot help but be affected by various socio-political factors within the wider Malaysian context. This is addressed in the present article in analysing bahasa Tanjong as the heritage language of the Jawi Peranakans using archival information, early 20th century data on Penang Malay, and contemporary bahasa Tanjong data.